External and Internal Quality of Duck Eggs That Are Storage O-14days in The Highlands of Bedugul - R., Rika; Wijana, I W.; Dewi, G. A. M. K. (Jurnal Peternakan Tropika, 2019)
This study aims to determine the effect of long storage time of the duck eggs which stored at room temperature in the highlands during 0-14 days regarding to external and internal quality. This research was conducted in the area of ??Bedugul and analyzed in the laboratory of the Faculty of Animal Husbandry Poultry of Udayana University for three weeks. Research design used was completely randomized design (CRD), which consists of three treatments, eggs without storage as control (R0), storage of 7 days (R7), and storage of 14 days (R14) that each treatment was using 5 replicates and each repetition uses 5 eggs. Variables observed that external quality include the egg weight and egg shape index, and internal quality include the thick cover of egg shell, egg shell weight, yolk color, haugh units (HU), and the pH of the egg. The results showed that egg weight, egg shape index, egg shell thickness, egg shell weight, yolk color, and pH eggs showed no significant results (P> 0.05) and the results of h augh unit (HU) eggs show results were significantly different (P <0.05). Based on the results of this study concluded that the storage of the duck eggs for 7 days and 14 days in the highlands area Bedugul not losing of eggs weight, the index of egg shape, thick egg shell, the weight of  eggs shell, color egg yolk and pH, but storage duck eggs for 14 days was losing the value of haugh units (HU), but it is still good for consumption by grade AA eggs. Keywords: duck eggs, long storage time, internal and external quality